The politics of legal pluralism in the shaping of spatial power in Myanmar's land governance. - Suhardiman, Diana; Bright, John; Palmano, Casper (Journal of Peasant Studies, 2021)
Following the National League for Democracy's landslide victory in the 2015 national election, Myanmar embarked on a series of legal and political transitions. This paper highlights parallel processes alongside such transitions. Linking land governance with the ongoing peace processes, and taking Karen state as a case study, it brings to light how both processes are in fact closely interlinked. Building on legal pluralism research, we argue that in the context of ethnic states, farmers' strategies to strengthen their land rights resemble the very notion of state transformation.